SCADA of an Upstream Controlled Irrigation Canal System - Rijo, Manuel (1999)
Upstream control in canals is efficient only when associated with rigid water delivery methods. In Portugal, all of the upstream controlled systems work with flexible water delivery schedules and, for this reason, operational water losses become significant. Because there is no storage reserve inside this kind of systems it is necessary to take into account the demand prediction or the command anticipation of the hydraulic control devices in order to improve the system response to demand variations. Real-time monitoring and control can hold an important key in this domain. These innovations allow the manager to react rapidly and effectively to the changing conditions of the system because, on one hand, they permit the manager to survey the real time hydraulic state of the system and, on the other hand, they permit the hydraulic state of the system to be corrected instantaneously. For these reasons, in Portugal, modernization of upstream controlled canals calls for remote monitoring and central control technologies. This paper presents the modernization program of the main canal system of the Sorraia Irrigation Project